Epoxynemanione A, nemanifuranones A–F, and nemanilactones A–C, from Nemania serpens, an endophytic fungus isolated from Riesling grapevines. (August 2017) - Ibrahim, Ashraf; Sørensen, Dan; Jenkins, Hilary A.; Ejim, Linda; Capretta, Alfredo; Sumarah, Mark W.
Abstract: Ten polyketide specialized metabolites, epoxynemanione A, nemanifuranones A–F, and nemanilactones A–C, were isolated from the culture filtrate of Nemania serpens (Pers.) Grey (1821), an endophytic fungus from a Riesling grapevine ( Vitis vinifera ) found in Canada's Niagara region. Additionally, four known metabolites 2-(hydroxymethyl)-3-methoxy-benzoic acid, phyllostine, 5-methylmellein and a nordammarane triterpenoid were isolated. A related known metabolite 2, 3-dihydro-2-hydroxy-2, 4-dimethyl-5- trans -propenylfuran-3-one has also been included for structural and biological comparison to the nemanifuranones. The latter was isolated from the culture filtrates of Mollisia nigrescens, an endophytic fungus from the leaves and stems of lowbush blueberry ( Vaccinium angustifolium ) found in the Acadian forest of Nova Scotia, Canada. Their structures were elucidated based on 1D and 2D NMR, HRESIMS measurements, X-ray crystallographic analysis of nemanifuranone A, the nordammarane triterpenoid and 2, 3-dihydro-2-hydroxy-2, 4-dimethyl-5- trans -propenylfuran-3-one compounds, and comparison of NOE and vicinal 1 H- 1 H coupling constants to literature data for relative stereochemical assignments. Nemanifuranone A possesses a rare C2 hemiacetal and was active against both Gram-negative and Gram-positive bacteria. Graphical abstract: Image 1 Highlights: Ten previously unknown and four known metabolites were isolated from the endophyte Nemania serpens. Nemanifuranones A-F contain a rare C2 hemiacetal group. Nemanifuranone A was active against Gram-negative and Gram-positive bacteria.